Gibran - Abubakar, Ayesah Uy
"Cultural boundaries are constructs of society that guides man to the right and acceptable action from what is not. But in the context of a society where different cultures meet, conflict of truths exist that affect every facet of human life. This Thesis is a documentary drama film titled "Gibran" that narrates the life of a Muslim child in a predominantly Christian community, taking into account the conflicts encountered in his everyday interactions and his adjustments to both the demands of society and beliefs and practices taught by his family. The film, set in Maharlika Village, Taguig, Bicutan, reflects the personal experience of the author in coping with the pressures of coexistence of two different difficulties affecting his way of life which is heavily influenced by his faith. The film starts with the act of "Sughbu" followed by the second episode of the noon-day muezzin call for "Dohor". Coming home from his friend's house, Gibran joins his mother for the 3:00 "Ashar" prayer and the next episode displays his interactions with his family as the time for Maghrib nears. The film culminates with the "Aisah" prayer, with Gibran performing the act of ablution"